Investigating the Relationship between Components of Pender's Health Promotion Model and Self-care Behaviors among Patients with Smear-positive Pulmonary Tuberculosis - Masoud Zare; Zakieh Asadi; Mohammad Vahedian Shahroodi; Hamidreza Bahrami-Taghanaki (Mashhad University of Medical Sciences, 2017)
Background: Tuberculosis is among the top ten causes of mortality across the world and is highly prevalent in Mashhad, Khorasan Razavi, Iran. The adoption of healthy behaviors by patients can prevent the transmission of this disease to other individuals. The Health Promotion Model is one of the models used in the field of behavior change in this regard. Aim: The aim of the present study was to investigate the relationship between the components of Pender's Health Promotion Model and self-care behaviors among the smear-positive pulmonary tuberculosis patients in Mashhad. Method: This correlational study was conducted on 144 smear-positive pulmonary tuberculosis patients, selected from 45 healthcare centers of Mashhad in 2015 using purposive sampling method. The research instruments included Self-Care Behavior Questionnaire, Components of Pender's Health Promotion Model, and Behavior Observation Checklist. The data were analyzed using Spearman's rank-order correlation coefficient through the SPSS software version 16. Results: According to the results of the study, the mean age of the patients was 51.9±21.1 years. The results also showed that the mean of self-care total score was equal to 63.7±7.3. Additionally, the Spearman's rank-order correlation indicated that self-care behavior was significantly correlated with prior related behavior (P=0.006), perceived barriers (P